An application of construction techniques in vernacular architecture used by indigenous people in Malaysia / Abdul Muhaimin Mohd Salleh and Dr. Zalina Samadi - Mohd Salleh, Abdul Muhaimin; Samadi, Zalina (College of Built Environment, 2023)
Bamboo has become a popular material choice in architecture and design project because of its sustainable qualities and hardwearing characteristics it has a higher compressive strength than concrete or wood, and rivals the tensility of steel.